Biographical narrative study of refugee students’ lived experiences at a selected South African university - Chiramba, Otilia Fortunate (My University, 2020)
Refugee studies is an area that has begun to gain prominence in Higher Education Studies because of an ever-increasing number of forced migrations, in all age groups. A significant number of these refugees aspire to pursue tertiary education. Existing studies have shown that refugee students form an invisible group within higher education spaces. Universities have failed to distinguish them from international students. Because of the concealment, refugee students face formidable challenges in navigating higher education due to lack of specific support meant to address their unique needs as refugees. Despite the growing body of scholarship, the field still lacks a comprehensive understanding of refugee students in at least two ways. Firstly, although the field has developed important insights into post-migration experiences of refugee students, very little is known about their pre-migratory experiences and intentions of future progression. Secondly, the literature focuses significantly on refugee students’ barriers to success, but has to a very large extent overlooked enablers that inform their success, despite the odds. This study has argued that creating sufficient value for refugee students in higher education requires a holistic understanding of their lived experiences across the three phases: pre-migration, post-migration and intentions of future progression. The study used an eclectic theoretical framework of push-pull, social justice and resilience theories, sequenced in a special way that served as a lens in the three phases of refugee students’ experiences. Based on a qualitative narrative inquiry which espoused the biographical narrative, four refugee students at a selected university in South Africa participated in the research involving cascading narrative interviews. These began with an unstructured interview and moved on to several follow-up semi-structured interviews. Data analysis deployed two techniques, starting with a narrative analysis, which helped to understand the unique experiences of each individual, ending with the thematic analysis which helped to understand the commonalities and differences that cut across the four individual biographies. Findings confirmed that the four refugee students did not only face structural and systemic challenges but they also exhibited internal and recurrent experiences of fear, dreams and resilience throughout the three phases. The study proposed a model: exogenous and endogenous dimensions: an integrated model of the lived experiences of refugees in higher education, as a basis for developing strategies for reforming policy for refugee students in higher education. Secondly, this model may help universities and host nations gain a comprehensive understanding of refugees in order to come up with useful and meaningful interventions. The analytical model developed can be a useful starting point to engage in further research studies for refugee students in higher education.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020